Energy efficiency strategies for residential buildings in a subarctic climate: Impacts on energy use and indoor thermal climate - Bhattacharjee, Shimantika (Luleå tekniska universitet, Industriellt och hållbart byggande, 2023)
Adopting energy efficiency strategies in residential buildings are beneficial as these not only improve the energy performance but also improves the indoor thermal climate and minimizes the greenhouse gas emissions. There exist numerous studies on energy efficiency strategies and their influence on indoor thermal climate in residential buildings in cold climates. However, there is a lack of documented and systematic studies that explicitly investigated the selection of appropriate energy efficiency strategies and their impact on the indoor thermal climate in residential buildings in a subarctic climate. Moreover, the impact of such energy efficiency strategies on the life cycle energy use of buildings has not been given appropriate attention in the existing literature. Due to the extreme climate conditions in a subarctic climate – severe cold and dark winter with heavy snow and mild short summer – buildings require a considerable amount of heating energy to maintain a comfortable temperature indoors. Therefore, it is important to adopt energy efficiency strategies that can help obtain operational and life cycle energy savings along with a better indoor thermal climate. The aim of this study is to evaluate the impact of different energy efficiency strategies on energy use and thermal indoor climate of three selected case study residential buildings in a subarctic climate. Three research questions were formulated: (1) What is the impact of evaluated energy‐efficiency strategies on the operational energy use?, (2) What is the impact of evaluated energy‐efficiency strategies on the life‐cycle energy use?, and (3) What is the impact of evaluated energy‐efficiency strategies on the thermal indoor climate? To address research questions 1 and 3, implemented energy‐efficiency strategies in two low‐energy buildings were evaluated using measured energy data and dynamic building energy and indoor climate simulations. To address research question 2, different combinations of energy efficiency strategies were explored using a ...